Checklist of free-living microturbellarian flatworms (Turbellaria, Platyhelminthes) in the Suquía River Basin, Córdoba, Argentina - Adami, Mariana Laura (2021)
Free-living microturbellarians are a part of lentic and lotic aquatic assemblages and play an important but underestimated role in aquatic ecosystems. Consequently, they are not included in studies on the dynamics of freshwater aquatic invertebrate communities. We report eight new records of microturbellarians from the Suquía River (Córdoba, Argentina): Catenula lemnae Dugès, 1832, Stenostomum arevaloi Gieysztor, 1931, Stenostomum aff. amphotum Marcus, 1945, Macrostomum aff. quiritium Beklemischev, 1951, Macrostomum platensis Adami, Damborenea & Ronderos, 2012, Microstomum sp., and Mesostoma erhenbergii (Focke, 1836). We discuss these results within the geomorphological history of the river basin.